Biophotonics for medical applications - Meglinski, Igor; ScienceDirect eBooks (Cambridge, UK : Woodhead Publishing is an imprint of Elsevier, 2015)
Biophotonics for Medical Applications presents information on the interface between laser optics and cell biology/medicine. The book discusses the development and application of photonic techniques that aid the diagnosis and therapeutics of biological tissues in both healthy and diseased states. Chapters cover the fundamental technologies used in biophotonics and a wide range of therapeutic and diagnostic applications. Presents information on the interface between laser optics and cell biology/medicineDiscusses the development and application of photonic techniques which aid the diagnosis.
4.2.7. Materials and applications4.3. Laser drilling; 4.3.1. Introduction; 4.3.2. Pulsed Nd:YAG laser drilling; 4.3.3. Other laser drilling processes; 4.4. Micromachining; 4.4.1. Introduction; 4.5. Surface texturing; 4.5.1. Introduction; 4.5.2. Formation of textured surfaces; 4.6. Conclusions; References; Part Two: Applications in therapeutics and diagnostics; Chapter 5: Biomedicine with surface enhanced Raman scattering (SERS); 5.1. Introduction; 5.2. Surface enhanced Raman scattering; 5.3. Theory of surface enhanced Raman scattering; 5.3.1. Electromagnetic SERS (EM-SERS) enhancement.
Online resource; title from PDF title page (ScienceDirect, viewed July 9, 2015).
Elsevier
Keywords: Biomedical engineering; Photobiology; Photonics; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biomedical engineering; Photobiology; Photonics; Diagnostic Imaging; Biosensing Techniques -- methods; Optical Imaging; Optics and Photonics -- methods; Photons; Electronic books